KANDUNGAN INFORMASI DAN PERBEDAAN ABNORMAL RETURN SEBELUM DAN SETELAH ANNUAL REPORT AWARD - Aristiawan, I G N Agung Dedy; Ardiana, Putu Agus (E-Jurnal Akuntansi; Vol 11 No 2 (2015), 2015)
Annual Report Award was an event to the provision of the award to the company which has a good information transparency of the annual financial report as one of the application of the good corporate governance concept. This study aimed to determine whether there is content information of Annual Report Award (ARA) announcements and the difference of abnormal returns before and after the announcement of ARA. The samples in this study is companies that gained champion 1st, 2th and 3rd and listed on the Indonesia Stock Exchange (BEI) from 2009 until 2012. There are 46 companies were then analyzed using t-test to determine whether there is content information and paired sample t-test to determine whether there is a difference of abnormal return before and after the announcement of ARA. The results showed that the ARA announcement contains no information and no significant abnormal return difference between before and after the announcement of ARA.
Keywords: information content; abnormal returns; annual report award